2014
DOI: 10.1152/ajpendo.00276.2014
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hormonal responses to isoenergetic high-intensity interval exercise and continuous moderate-intensity exercise

Abstract: This study investigated the effects of high-intensity interval training (HIIT) vs. work-matched moderate-intensity continuous exercise (MOD) on metabolism and counterregulatory stress hormones. In a randomized and counterbalanced order, 10 well-trained male cyclists and triathletes completed a HIIT session [81.6 Ϯ 3.7% maximum oxygen consumption (V O2 max); 72.0 Ϯ 3.2% peak power output; 792 Ϯ 95 kJ] and a MOD session (66.7 Ϯ 3.5% V O2 max; 48.5 Ϯ 3.1% peak power output; 797 Ϯ 95 kJ). Blood samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 66 publications
12
146
1
10
Order By: Relevance
“…In general, we did not observe substantial changes in plasma amino acids immediately after the three exercise protocols. Alanine increased in all three types of exercise which is in accordance with most previous studies that used either short or prolonged endurance exercise protocols 12,[51][52][53] . Based on previous studies, the increase in plasma alanine seems likely the result of an excessive pyruvate accumulation in the muscle as part of the TCAi pool anaplerotic reactions and the activation of alanine-glucose cycle to replenish the carbohydrate/glycogen supplies 48,53 .…”
Section: Amino Acid Metabolismsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, we did not observe substantial changes in plasma amino acids immediately after the three exercise protocols. Alanine increased in all three types of exercise which is in accordance with most previous studies that used either short or prolonged endurance exercise protocols 12,[51][52][53] . Based on previous studies, the increase in plasma alanine seems likely the result of an excessive pyruvate accumulation in the muscle as part of the TCAi pool anaplerotic reactions and the activation of alanine-glucose cycle to replenish the carbohydrate/glycogen supplies 48,53 .…”
Section: Amino Acid Metabolismsupporting
confidence: 91%
“…Therefore, metabonomics is being increasingly used to examine the metabolic stress to a single exercise bout [7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, catecholamine-induced increases in lipolysis and metabolism (Zouhal et al 2008) may have been more pronounced with longer compared with shorter sprint bouts (Trapp et al 2007). Although this lipolytic effect has not always been reported (Williams et al 2013), several studies have shown increases in catecholamines (Trapp et al 2007;Williams et al 2013), free fatty acids (Peake et al 2014), and glycerol (McCartney et al 1986;Trapp et al 2007) after intense intermittent exercise, all of which are indicative of increased fat oxidation (Whyte et al 2010;Chan and Burns 2013;Beaulieu et al 2015). These observations are further supported by the improvements in muscle fat oxidative capacity achieved after training (Burgomaster et al 2008;Perry et al 2008;Gillen et al 2013Gillen et al , 2014.…”
Section: Discussionmentioning
confidence: 86%
“…A wide range of metabolites present in plasma and serum has been determined using liquid chromatography mass spectrometry and/or gas-chromatography mass spectrometry collected pre-and post-exercise. In most cases, a wide range of metabolites have been reported (Pohjanen et al 2007, Lewis et al 2010, Peake et al 2014 to exist and that with exercise changes in metabolites related to carbohydrate, triglyceride and markers of the tricarboxylic acid have been reported. Peake et al (2014), these studies were not hypothesis driven and are more observational in nature.…”
Section: Figurementioning
confidence: 99%
“…In most cases, a wide range of metabolites have been reported (Pohjanen et al 2007, Lewis et al 2010, Peake et al 2014 to exist and that with exercise changes in metabolites related to carbohydrate, triglyceride and markers of the tricarboxylic acid have been reported. Peake et al (2014), these studies were not hypothesis driven and are more observational in nature. However, the use of metabolomics could provide a unique insight into the co-ordinated metabolic response to exercise in terms of substrate mobilisation, utilisation and the production of metabolic by-products.…”
Section: Figurementioning
confidence: 99%